2022
DOI: 10.3390/metabo12060543
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Major Brain Metabolites in Normal Adults: Short Echo Time Whole-Brain MR Spectroscopic Imaging Findings

Abstract: This prospective study aimed to evaluate the variation in magnetic resonance spectroscopic imaging (MRSI)-observed brain metabolite concentrations according to anatomical location, sex, and age, and the relationships among regional metabolite distributions, using short echo time (TE) whole-brain MRSI (WB-MRSI). Thirty-eight healthy participants underwent short TE WB-MRSI. The major metabolite ratios, i.e., N-acetyl aspartate (NAA)/creatine (Cr), choline (Cho)/Cr, glutamate + glutamine (Glx)/Cr, and myoinositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…WB-MRSI was processed using Metabolic Imaging and Data Analysis System (MIDAS) software version 2.35 (University of Miami, Miami, FL, USA) running on IDL version 8.4.1 (Exelis Visual Information Solutions, Boulder, CO, USA) [ 30 ]. The same procedures were applied to all participants (i.e., TBI patients and control subjects [ 26 ]). The workflow and processing steps are summarized in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…WB-MRSI was processed using Metabolic Imaging and Data Analysis System (MIDAS) software version 2.35 (University of Miami, Miami, FL, USA) running on IDL version 8.4.1 (Exelis Visual Information Solutions, Boulder, CO, USA) [ 30 ]. The same procedures were applied to all participants (i.e., TBI patients and control subjects [ 26 ]). The workflow and processing steps are summarized in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between the MRI measure (i.e., mode of brain temperature or metabolite ratios) and cognitive function test scores was evaluated using partial correlation analysis in the TBI group. Our previous study on the normal database showed a variation in brain metabolite concentration with aging [ 26 ]. In addition, a considerable variation in the time lapsed from trauma was observed in the patients.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid further confounding effects, the three study groups were also similar with respect to age and PTA values (although we failed to exclude hearing loss cases completely). Both these factors have been found to in uence metabolite levels in CNS 78, [113][114][115][116] . We were also the rst ones in human MRS research, to divide the groups based on tinnitus status and laterality.…”
Section: Tinnitus Heterogeneity and Participants' Inclusionmentioning
confidence: 99%
“…N-acetylaspartate (NAA) is used in magnetic resonance spectroscopy as a biomarker of neuronal health, integrity, and viability [ 14 ]. Using ratios between these metabolites instead of their absolute concentrations is more common in routine clinical practice due to their simpler acquisition and processing [ 15 ].…”
Section: Introductionmentioning
confidence: 99%